Efeitos da administração local do ácido tiludrônico na periodontite experimental em ratos diabéticos - Nunes, Nara Lhays Teixeira (2015)
The bisphosphonate tiludronic acid (TIL) presents anti-resorptive and anti-inflammatory properties and it has not been evaluated in the association periodontitis-diabetes mellitus (DM) to date. The purpose of this study was to evaluate the effects of local administration of TIL on experimental periodontitis (EP) in rats with streptozotocin (STZ)-induced DM. On day 1, thirty two rats received STZ injection. The animals were divided into groups (n=8): DM/C (Control), DM/EP, DM/EP/TIL1 and DM/EP/TIL3. In groups EP, a ligature was placed around the cervical area of mandibular first molars at day 8. In groups DM/EP/TIL1 and DM/EP/TIL3, TIL solutions of 1 and 3 mg/kg body weight, respectively, were injected into the buccal gingival margin of mandibular first molars every other day. Animals were euthanized at day 18. Histomorphometric analyses were performed. Data were statistically analyzed (p<0.05). Group DM/EP/TIL3 presented reduced alveolar bone loss and attachment loss when compared with group DM/EP (p<0.05). Within the limits of this study, it can be concluded that i) the local administration of TIL solutions presented a protective effect on tissue destruction in EP in diabetic rats and ii) the dosage of TIL may influence its effects.